Automated information sharing in foster care: perspectives on impact and expansion - Nathan M. Lutz; Nathan M. Lutz; Mary V. Greiner; Mary V. Greiner; Lisa Vaughn; Amanda Schondelmeyer; Elizabeth Freehling; Katie Fox; Sarah J. Beal; Sarah J. Beal; Sarah J. Beal (Frontiers in Pediatrics)
IntroductionFor youth in foster care, healthcare information is often not communicated to relevant individuals, including foster caregivers and healthcare staff. Technology solutions designed to bridge that gap have been shown to increase information available, decrease time spent searching for information, and improve access to services. The feasibility of technology-based information sharing has been demonstrated with caseworkers.MethodsThis qualitative study builds upon existing knowledge about the benefits of technology-based information exchange systems, utilizing interviews with healthcare staff (n = 41) and foster caregivers (n = 7). The purpose of this work is to understand their perspectives related to the utility of information-exchange technology, barriers faced, and potential improvements.ResultsThree themes were identified: (1) Impact and Benefits: The high-yield benefits of automated, on-demand information-sharing platforms for children in foster care; (2) User Experience and Efficiency: Streamlined workflows and improved outcomes; and (3) Opportunities for Platform Expansion: How information sharing can be further improved. Healthcare staff and caregivers alike said using technology to share health and child welfare information was efficient and easy in a system that is fragmented. They also identified opportunities for expansion, such as including more sources of information (e.g., information from caregivers themselves).DiscussionThese findings add to the evidence that information exchange platforms in child welfare increase the capacity of healthcare staff and caregivers while decreasing workload in an otherwise overburdened system. Expanding access to and use of information-exchange platforms in healthcare settings that serve youth in foster care may support the workforce who serve these children.